Newly Developed Method for Determination Indomethacin using Potassium Hexacyanoferrate (III) by using ISNAG-Fluorimeter Homemade via CFIA - Proph Nagam Shakir Turkie (Journal of Global Pharma Technology, 2018)
A new, simple, sensitive and fast developed method for the determination of Indomethacin in pure form and drugs (capsule) by continuous flow injection diverged light. The method based on the reaction of the Indomethacin with Potassium hexacyanoferrate (III) to form off-white precipitate, using homemade ISNAG- fluorimeter. Optimum parameter has been studied to increase the sensitivity for developed method. The linear dynamic range for the instrument response versus Indomethacin concentration was 0.01- 5mmol/L while the L.O.D was 320.222ng/sample from the step wise dilution for the minimum concentration of lowest concentration in the linear dynamic range of the calibration graph. The correlation coefficient (r) was 0.9952while percentage linearity (R2%) was 99.05%. RSD% for the repeatability (n=7) was lower than 0.5% for the determination of Indomethacin, with concentration of 1, 5 mmol/L respectively. The methods: developed method was applied successfully for the determination of Indomethacin in pharmaceutical tablets. A comparison was made between the newly developed methodology and the classical method (turbidometry) of analysis using the standard addition method via the use of paired t-test. It shows that there was no significant difference between the quoted values of each individual company with calculated t-value at 95% confidence interval from developed method.Keywords: Indomethacin, flow injection diverged light, homemade instrument.